COLLECTIVE MEMORY AND TRANSLATION:: IDEOLOGICAL ADAPTATIONS IN THE GERMAN AND PORTUGUESE TRANSLATIONS OF THE DIARY OF ANNE FRANK - Sepp, Arvi; Marie Humblé, Philippe René (Revista de Letras, 2025)
This article examines how translations of Anne Frank’s Diary shape collective memory through ideological adaptations. Focusing on the German context, it compares Anneliese Schütz’s 1950 version with Mirjam Pressler’s 1991 edition, situating both within Germany’s Vergangenheitsbewältigung. Schütz’s translation “de-Judaizes” and “de-Germanizes” the text by softening references to antisemitic laws, omitting “Vollblut-Juden,” reducing occurrences of “Jude/Deutsch,” and smoothing family conflicts and Anne’s youthful voice—effects that blur historical and moral specificity; Pressler moves the text closer to the original. In the GDR, an official antifascist frame encouraged universalizing readings. In the Lusophone sphere, the study maps Portuguese (Losa, 1958; Vieira, 2004) and Brazilian editions (Edel, 1978; Calado, 2004; Mariano, 2017; Prado/Paiva, 2019; Zwiesele, 2019), highlighting juvenilizing prefaces and the recurrent shift from present to imperfect tense, which distances the experience and softens the diary’s urgency. The article concludes that translational and paratextual choices respond to market expectations and memory politics, thereby shaping the historical, ethical, and literary reception of the Diary.